Designing a Web-Based Student Attendance Information System Using Extreme Programming Methods at the Bandung Praktisi Polytechnic - Yudhi Yanuar; Ari Waluyo (Politeknik Piksi Ganesha Indonesia, 2023)
This research aims to design a student attendance information system. In developing the information system, we used the method of observing research objects and conducting literature studies. We used object-oriented modelling with UML tools to describe the student attendance information system. In addition, extreme programming was used to develop the student attendance information system. In creating a student attendance information system using the PHP and MySQL programming languages as the System Management Database, the test results of the student attendance information system at the practitioner Polytechnic can be used well and effectively.